2017
DOI: 10.15291/geoadria.55
|View full text |Cite
|
Sign up to set email alerts
|

Geomorfološka obilježja doline i poriječja rijeke Krke s osvrtom na dio od Knina do Bilušića buka

Abstract: Rijeka Krka sa svojim pritocima čini sustav kompozitnih dolina u kršu. Kompozitnost dolina posljedica je litoloških i tektonskih odnosa. Dolina Krke poligenetskog je postanka. Za kanjonske dijelove karakteristična je pojava brojnih padinskih reljefnih detalja. Na strmijim padinama izrazito je osipanje i urušavanje. U aluvijalnim nanosima u dolinskim proširenjima nađeni su fragmenti kršja okolnih stijena. U novije doba uočava se regeneracija vegetacije koja pridonosi promjeni intenziteta modeliranja reljefa egz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Although nutrient level and physicochemical measurements (low COD, constant high oxygen saturation) confirmed Krčić as a pristine ecosystem, with year-long oligotrophic nutrient status, at the same time, this river showed intense seasonal fluctuations in its water regime. Longterm hydrological measurements on several gauging stations already affirmed the cyclic periodicity of the Krčić river brought on by summer droughts (Bonacci et al, 2006) and erratic but substantial rainfall periods (850-1750 mm along Krka River; Penzar & Penzar, 1990;Perica et al, 2005 previously reported in different environments, but with clear preference for carbonate-rich waters and unpolluted freshwater environments (Komárek, 1992;Margheri, Piccardi, Ventura, Viti & Giovannetti, 2003;Tavera, Novelo, & Lopez, 2013;Brinkmann et al, 2015). The dominance of cyanobacteria in this karst ecosystem concurred with similar research conducted on German karsts (Arp et al, 2010;Schneider et al, 2015).…”
Section: Diversity Indicessupporting
confidence: 88%
See 4 more Smart Citations
“…Although nutrient level and physicochemical measurements (low COD, constant high oxygen saturation) confirmed Krčić as a pristine ecosystem, with year-long oligotrophic nutrient status, at the same time, this river showed intense seasonal fluctuations in its water regime. Longterm hydrological measurements on several gauging stations already affirmed the cyclic periodicity of the Krčić river brought on by summer droughts (Bonacci et al, 2006) and erratic but substantial rainfall periods (850-1750 mm along Krka River; Penzar & Penzar, 1990;Perica et al, 2005 previously reported in different environments, but with clear preference for carbonate-rich waters and unpolluted freshwater environments (Komárek, 1992;Margheri, Piccardi, Ventura, Viti & Giovannetti, 2003;Tavera, Novelo, & Lopez, 2013;Brinkmann et al, 2015). The dominance of cyanobacteria in this karst ecosystem concurred with similar research conducted on German karsts (Arp et al, 2010;Schneider et al, 2015).…”
Section: Diversity Indicessupporting
confidence: 88%
“…Although nutrient level and physicochemical measurements (low COD, constant high oxygen saturation) confirmed Krčić as a pristine ecosystem, with year‐long oligotrophic nutrient status, at the same time, this river showed intense seasonal fluctuations in its water regime. Long‐term hydrological measurements on several gauging stations already affirmed the cyclic periodicity of the Krčić river brought on by summer droughts (Bonacci et al, ) and erratic but substantial rainfall periods (850–1750 mm along Krka River; Penzar & Penzar, ; Perica et al, ). Based on measured hydrological conditions and observed disturbances exerted onto the microbial mat community, periodicity of the Krčić river can be divided into (a) drought period generated during summer season, (b) strong rains following in the autumn months, (c) freezing ambient temperature during winter period, and (d) higher water levels reached in the spring time as a consequence of snow melt.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations